Plagiarism in academic writing among students of higher learning institutions in Malaysia. - Zejno, Bukuri; Ismail, Nik Ahmad Hisham; Shehu, Fatmir Mehdi (Institut Terjemahan dan Buku Malaysia, 2016)
Plagiarism through the use of technology in education. To investigate attitude towards plagiarism among postgraduate students of selected universities in Malaysia.